Pembuatan Kompos dari Limbah Kulit Pinang di Desa Sido Mukti Kecamatan Dendang Kabupaten Tanjung Jabung Timur - Panjaitan, Arda Trisnawaty; Manullang, Fanny Angelika; Manullang, Friska Mawira; Nahampun, Widya Patricia Utama; Hidayah, Nurul (Jurnal Pengembangan dan Pengabdian Masyarakat, 2026)
Areca nut husk waste is one of the abundant organic wastes in Sido Mukti Village but has not been utilized optimally and tends to pollute the environment. This community service program aims to address this problem by providing training on compost production. The method used involves a simple fermentation process with the aid of EM4 microbial activator, livestock manure, and bran to accelerate the decomposition of organic materials. Through the implementation of this program, 12 kg of areca nut husk waste was processed into 55 kg of high-quality compost characterized by dark brown color, crumbly texture, and earthy aroma. This compost has been utilized by local farmers for horticultural cultivation, such as chili, long beans, water spinach, and mustard greens, resulting in a 20% increase in productivity. Program evaluation was conducted and field observations, showing an 80% improvement in community understanding of organic waste management. These results demonstrate that composting areca nut husk waste not only helps solve organic waste problems but also supports environmental sustainability and improves local farmers’ welfare.